Sets or frequencies? How to explain the facilitation effect in conditional probability problems - Moro, Rodrigo; Bodanza, Gustavo Adrián (Anales de Psicología / Annals of Psychology, 2010)
Since the ’70s, the Heuristics and Biases Program in Cognitive Psychology has shown that people do not reason correctly about Bayesian or conditional probability problems. In the ’90s, however, evolutionary psychologists discovered that if the same problems are presented in a different way, people’s performance greatly improves. Two explanations have been offered to account for this facilitation effect: the natural frequency hypothesis and the nested-set hypothesis. The empirical evidence on this debate is mixed. We review the literature and offer a clarification of the debate in terms of strategies and techniques used by the researchers in the area. We argue that the provided evidence seems to favor the nested-set hypothesis. However, we also argue that there is still room for disagreement and more empirical work is needed to settle the issue.